EFEKTIVITAS ADMINISTRASI PELAYANAN PUBLIK DI KANTOR KELURAHAN TANJUNG SELOR TIMUR KECAMATAN TANJUNG SELOR KABUPATEN BULUNGAN - Imam Muazansyah; Indah Sari (Faculty of Social and Political Science, 2022)
The services provided by the government have received a sharp scrutiny from the people themselves. Service is the main goal to create the best service for the whole community. Poor public services are not new, the problem is that public services are not yet optimal, the services are not yet effective, which results in excellent service not being realized. This made the researchers interested in conducting research with the aim of research to find out and describe the administration of public services in the East Tanjung Selor Village office, Tanjung Selor District, Bulungan Regency. This research method uses a qualitative descriptive research method. The data sources used are primary data, namely informants and secondary data including book references, previous research, government regulations related to public service administration. Data collection techniques were carried out through observation, interviews and documentation. The research focus is based on PERMENPANRB Number 15 of 2014. Data analysis uses four components, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the data analysis carried out, it was concluded that the public services carried out by the Tanjung Selor Timur sub-district were quite effective by providing services according to the SOP (Service Operational Standards) carried out to the community even though there was still a lack of human resources in providing services but the community was quite satisfied with the service. received from the municipality